Está en la página 1de 2

Porubaix Cd - C - H2O

Porubaix C - H2O

5C

5C

Cd(+2a)+CO2(a)+H2O=CdCO3+2H(+a)

C+2H2O=CO2(a)+4H(+a)+4e-

Cd(+2a)+C+3H2O=CdCO3+6H(+a)+4e-

C+4H(+a)+4e-=CH4(a)

Cd(+2a)+CH4+3H2O=CdCO3+10H(+a)+8e-

C+3H2O=HCO3(-a)+5H(+a)+4e-

Cd(OH)2+CH4+H2O=CdCO3+8H(+a)+8e-

C+3H2O=CO3(-2a)+6H(+a)+4e-

Cd(OH)2+CO3(-2a)+2H(+a)=CdCO3+2H2O

CH4(a)+3H2O=CO3(-2a)+10H(+a)+8eCO2(a)+H2O=HCO3(-a)+H(+a)
HCO3(-a)=CO3(-2a)+H(+a)

25C
Cd(+2a)+H2CO3(a)=CdCO3+2H(+a)
Cd(+2a)+C+3H2O=CdCO3+6H(+a)+4e-

25C

Cd(+2a)+CH4+3H2O=CdCO3+10H(+a)+8e-

C+3H2O=H2CO3(a)+4H(+a)+4e-

Cd(OH)2+CH4+H2O=CdCO3+8H(+a)+8e-

C+4H(+a)+4e-=CH4(a)

Cd(OH)2+CO3(-2a)+2H(+a)=CdCO3+2H2O
95C

C+3H2O=HCO3(-a)+5H(+a)+4eCH4+3H2O=HCO3(-a)+9H(+a)+8eCH4(a)+3H2O=CO3(-2a)+10H(+a)+8e-

Cd(+2a)+CO2(a)+H2O=CdCO3+2H(+a)

H2CO3(a)=HCO3(-a)+H(+a)

Cd(+2a)+C+3H2O=CdCO3+6H(+a)+4e-

HCO3(-a)=CO3(-2a)+H(+a)

Cd(+2a)+CH4+3H2O=CdCO3+10H(+a)+8eCd(OH)2+CH4+H2O=CdCO3+8H(+a)+8e-

95C

Cd(OH)2+CO3(-2a)+2H(+a)=CdCO3+2H2O

C+2H2O=CO2(a)+4H(+a)+4eC+4H(+a)+4e-=CH4(a)
C+3H2O=HCO3(-a)+5H(+a)+4eCH4+3H2O=HCO3(-a)+9H(+a)+8eCH4(a)+3H2O=CO3(-2a)+10H(+a)+8eCO2(a)+H2O=HCO3(-a)+H(+a)
HCO3(-a)=CO3(-2a)+H(+a)

a 25C aparece la especie H2CO3(a) en lugar de CO2(a)

Porubaix Cd - H2O
5C
Cd2+

Cd2+ + 2e- = Cd(s)


+ 2H2O = Cd(OH)2 + 2H+

Cd(s) + 2H2O = Cd(OH)2 + 2H+ + 2eCd(OH)2 + 2H2O = Cd(OH)42- + 2H+


Cd(s) + 4H2O = Cd(OH)42- + 4H+ + 2e25C
Cd2+

Cd2+ + 2e- = Cd(s)


+ 2H2O = Cd(OH)2 + 2H+

Cd(s) + 2H2O = Cd(OH)2 + 2H+ + 2eCd(OH)2 + 2H2O = Cd(OH)42- + 2H+


Cd(s) + 4H2O = Cd(OH)42- + 4H+ + 2e95C
Cd2+

Cd2+ + 2e- = Cd(s)


+ 2H2O = Cd(OH)2 + 2H+

Cd(s) + 2H2O = Cd(OH)2 + 2H+ + 2eCd(OH)2 = CdO22- + 2H+


Cd(s) + 2H2O = CdO22- + 4H+ + 2e-

a 95C la especie CdO2(-2a) reemplaza a Cd(OH)4(-2a)